Intranasal Immunization with DNA Vaccine HA-CCL19/Polyethylenimine/Chitosan Composite Provides Immune Protection Against H7N9 Infection - Yuqing Xiang; Hongbo Zhang; Youcai An; Ze Chen (Vaccines)
Background/Objectives: The H7N9 avian influenza virus (AIV) constitutes a novel subtype of influenza virus that has emerged within the past decade. Empirical studies have demonstrated that H7N9 AIV holds the potential to trigger a human pandemic. Vaccines constitute the sole armament available to humanity in combating influenza epidemics. DNA vaccines present numerous merits; however, substantial conundrums persist regarding how to augment their immunogenicity and implement their delivery through mucosal immunization. Methods: In this study; BALB/c mice were utilized as a model to investigate the effect of CCL19 as a molecular adjuvant and to determine the immune response elicited by polyethylene imine (PEI) and chitosan (CS) as adjuvants during the delivery of a DNA vaccine through the nasal mucosal route. Results: Our results revealed that the CCL19 molecular adjuvant exerts a substantial immunomodulatory enhancement effect on the H7N9-HA DNA vaccine, inducing more pronounced cellular and humoral immunity. Additionally, our results indicated that the composite formed by the HA-CCL19 DNA in combination with PEI and CS effectively activates local mucosal immunity as well as systemic humoral and cellular immunity, offering 100% protection against lethal doses of homologous virus challenges. Conclusions: CCL19 conspicuously augments the immunogenicity of the influenza virus HA DNA and conserves the integrity of the vaccine antigen. Simultaneously, CS and PEI proficiently facilitate the mucosal delivery of DNA, thereby eliciting mucosal immunity related to DNA vaccines. This study investigated the feasibility of utilizing nasal mucosa for DNA vaccine immunization, which holds significant implications for the advancement and application of DNA vaccines in public health